2006
DOI: 10.1093/occmed/kql097
|View full text |Cite
|
Sign up to set email alerts
|

Work-related asthma symptoms and attitudes to the workplace

Abstract: Workers' perception of risk influences their behaviour in the workplace, and their own health beliefs potentially create barriers to changing this. It is essential to consider workers' perceptions when developing strategies to effect change within the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…Reproduction prohibited http://www.thepcrj.org C o p y r i g h t G e n e r a l P r a c t i c e A i r w a y s G r o u p R e p r o d u c t i o n p r o h i b i t e d example, previous work has shown that workers may not be accurate when completing health surveillance questionnaires. 24 Qualitative data from this current study also suggests that workers with possible occupational asthma have complex and largely negative attitudes to and perceptions of the workplace, 8 factors that are also likely to influence reporting of work related symptoms.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Reproduction prohibited http://www.thepcrj.org C o p y r i g h t G e n e r a l P r a c t i c e A i r w a y s G r o u p R e p r o d u c t i o n p r o h i b i t e d example, previous work has shown that workers may not be accurate when completing health surveillance questionnaires. 24 Qualitative data from this current study also suggests that workers with possible occupational asthma have complex and largely negative attitudes to and perceptions of the workplace, 8 factors that are also likely to influence reporting of work related symptoms.…”
Section: Discussionmentioning
confidence: 73%
“…In this context, the documented failure of patients to accept and understand the diagnosis given may not only reflect communication difficulties but also the complex interaction between personal perceptions of ill health within the workplace dynamics. 8 This study has clear shortcomings. Recall bias may have affected the patients' ability to report the onset and various assessments of their respiratory symptoms by health care workers, and may influence the interpretation of these findings.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Flour dust exposure continues to cause occupational asthma in the UK [Brant et al, 2005a], a condition known to have significant medical, workplace [Bradshaw et al, 2007] and economic consequences [Larbanois et al, 2002], almost certainly as a consequence (at least) of continuing high levels of exposure [Elms et al, 2005].…”
Section: Introductionmentioning
confidence: 99%